Low temperature degradation of laser patterned 3Y-TZP: Enhancement of resistance after thermal treatment. Issue 4 (April 2018) - Roitero, E.; Ochoa, M.; Anglada, M.; Mücklich, F.; Jiménez-Piqué, E.
Abstract: The aim of this study is to characterize the resistance to low temperature degradation (LTD) of the surface of dental-grade zirconia (3Y-TZP) patterned with a Nd:YAG laser (532 nm harmonic and pulse duration of 10 ns) employing an interference setup. Laser patterning decreases the resistance to LTD of 3Y-TZP because of the presence of monoclinic phase and residual stresses, induced by the thermal shock during laser-material interaction. A thermal treatment (1 h at 1200 °C) anneals the affected microstructure and increase the resistance to LTD of laser patterned 3Y-TZP. Transformation delay may be attributed to monoclinic phase reversion, texture in the tetragonal phase and the existence of a net of shallow microcracks on the surface, accommodating autocatalytic transformation.